Lithium supplement diaphragm, preparation method thereof and lithium ion battery

By using a composite material of alumina-loaded cobalt, carbon nanotubes and lithium sulfide on the lithium-ion battery separator, the problem of poor thermal stability of the separator at high temperatures is solved, and the safety performance, rate performance and energy density of the battery are improved.

CN119651057APending Publication Date: 2025-03-18HUADING GUOLIAN SICHUAN POWER BATTERY CO LTD
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202510037054.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-09
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

The existing lithium-ion battery separators have poor thermal stability at high temperatures, which affects safety performance; at the same time, the prelithium layer of the existing lithium-complement separators has little bonding force with the separator matrix, which affects stability, and the inorganic protective layer reduces the ionic conductivity of the battery cell and affects the rate performance.

Method used

The composite material of alumina-loaded cobalt, carbon nanotubes and lithium sulfide is used as the coating for the lithium-enhancing separator. The separator is prepared by liquid precipitation, reduction, vapor deposition and spraying method to improve its thermal stability and lithium ion transport speed.

Benefits of technology

It significantly improves the thermal stability of the diaphragm, enhances the transmission speed of lithium ions, and improves the safety performance, rate performance and energy density of lithium ion batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119651057A_ABST
    Figure CN119651057A_ABST
Patent Text Reader

Abstract

The invention provides a lithium supplement diaphragm, a preparation method thereof and a lithium ion battery, and relates to the technical field of lithium ion batteries. The lithium supplementing diaphragm comprises a base membrane and a lithium supplementing coating attached to at least one face of the base membrane, and the lithium supplementing coating comprises aluminum oxide loaded cobalt, a carbon nano tube and lithium sulfide. Aluminum oxide can remarkably improve the thermal stability of the diaphragm and inhibit shrinkage of the diaphragm at high temperature, lithium sulfide serves as a lithium supplementing agent and can achieve the lithium supplementing effect, cobalt and sulfur are combined to form stable sulfide in the lithium supplementing process, accordingly, electrochemical inertia is kept after lithium supplementing is completed, stable lithium supplementing is achieved, and the carbon nano tubes have selective permeability on lithium ions, so that the lithium-ion battery diaphragm can be applied to lithium ion batteries. And as a conductive framework, rapid migration of electrons and ions can be promoted, and the rapid charging performance of the lithium ion battery can be enhanced, so that the lithium ion battery integrates the safety performance, the energy density and the rapid charging performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium ion battery diaphragms, and in particular to a lithium supplement diaphragm and a preparation method thereof, and a lithium ion battery. Background Art

[0002] As an important component of lithium-ion batteries, the diaphragm plays the role of electronic insulation between the positive and negative electrodes, while ensuring the free movement of ions. Although the diaphragm does not directly participate in the electrochemical reaction of the battery, its structure and performance play an important role in battery safety, fast charging performance and energy density.

[0003] In terms of safety performance, it is usually improved by coating the surface with an inorganic coating. Polyolefin diaphragms include polyethylene diaphragms and polypropylene diaphragms. The melting points of polypropylene and polyethylene are 165°C and 135°C, respectively. They have poor thermal stability. When the battery temperature rises abnormally, it will cause the diaphragm to shrink and melt, and the safety performance is poor. Among them, nano-alumina is an inorganic ceramic particle commonly used as a coating material for lithium-ion battery diaphragms. It has high thermal stability and chemical inertness, and has excellent high temperature resistance. It can greatly improve the safety of lithium-ion batteries. In addition, it can neutralize free HF in the electrolyte and increase the service life of the battery. In addition, the dense nano-alumina coating on the surface of the ceramic diaphragm can improve the wettability of the electrolyte, but the dense nano-alumina coating and the insulation of nano-alumina will affect the transmission of lithium ions.

[0004] In terms of fast charging performance, the thickness, porosity and air permeability of the diaphragm have a great influence on the fast charging of lithium-ion batteries. When the thickness is thin, the porosity is large, and the air permeability is high, the barrier to the transfer of lithium ions from the positive electrode to the negative electrode is small, and the polarization effect during the charging process is small. The thickness and porosity of the diaphragm affect the charging performance of lithium-ion batteries. When designing fast-charging batteries, thin and high-porosity diaphragms are generally selected, but the safety performance of diaphragms that are too thin and have too high porosity is difficult to guarantee.

[0005] In terms of energy density, it has been reported that a lithium supplement layer is provided on the diaphragm to improve energy density, and inorganic materials such as metals and metal compounds are provided on the surface of the lithium supplement layer as a protective layer. However, the bonding force between the pre-lithium layer and the diaphragm matrix in the existing lithium supplement diaphragm is relatively small, which affects the stability of the lithium supplement diaphragm. In addition, the inorganic protective layer in the existing lithium supplement diaphragm has a low porosity after the battery is assembled, which affects the ionic conductivity of the battery cell after assembly, and further affects the rate performance of the battery cell.

[0006] Therefore, it is necessary to provide a new type of lithium supplement membrane that allows lithium ions to take into account safety performance, rate performance and energy density. Summary of the invention

[0007] In view of the deficiencies of the prior art, the present invention provides a diaphragm to improve the thermal stability and lithium ion transmission speed of the diaphragm and increase the lithium replenishment function, so that the lithium ion battery using the diaphragm has both safety performance, rate performance and energy density.

[0008] One of the purposes of the present invention is to provide a lithium supplementing diaphragm.

[0009] The second object of the present invention is to provide a method for preparing the lithium supplementing diaphragm.

[0010] A third object of the present invention is to provide a lithium-ion battery comprising the lithium-supplementing diaphragm.

[0011] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:

[0012] In a first aspect, the present invention provides a lithium replenishing diaphragm, comprising a base film and a lithium replenishing coating attached to at least one side of the base film, wherein the components of the lithium replenishing coating include aluminum oxide loaded with cobalt, carbon nanotubes and lithium sulfide, wherein the carbon nanotubes are attached to metallic cobalt.

[0013] In a second aspect, the present invention provides a method for preparing a lithium supplementing diaphragm, such as Figure 1 As shown, the following steps are included:

[0014] Step S1: using aluminum oxide and cobalt salt as raw materials, preparing aluminum oxide-supported cobalt hydroxide by liquid phase precipitation method;

[0015] Step S2: heating the alumina-supported cobalt hydroxide obtained in step S1, and preparing alumina-supported cobalt metal by a reduction method;

[0016] Step S3: using the alumina-supported cobalt metal obtained in step S2 as a raw material, adding a carbon source, and reducing and depositing carbon nanotubes on the alumina-supported cobalt metal by chemical vapor deposition to obtain an alumina-supported cobalt / carbon nanotube composite material;

[0017] Step S4: uniformly mix the alumina-loaded cobalt / carbon nanotube composite material obtained in step S3 with a dispersant, lithium sulfide, and a binder, and spray the mixture onto at least one side of the base film to obtain a lithium-supplementing separator.

[0018] The following is a detailed description of each step:

[0019] Step S1: preparing alumina-supported cobalt hydroxide by liquid phase precipitation method.

[0020] In some embodiments, step S1 comprises the following steps:

[0021] Alumina (Al2O3) powder and cobalt salt are placed in a beaker, deionized water is added thereto, and they are dispersed evenly by ultrasound. Subsequently, a sodium hydroxide (NaOH) aqueous solution is slowly added to the dispersed liquid, and alumina-loaded cobalt hydroxide (Al2O3 / Co(OH)2) is generated during the slow dropwise precipitation process.

[0022] Preferably, the cobalt salt in step S1 is one or more soluble salts such as cobalt chloride, cobalt sulfate, and cobalt nitrate;

[0023] Preferably, the molar ratio of aluminum oxide to cobalt salt is 1-2:1-2;

[0024] Preferably, the concentration of the sodium hydroxide (NaOH) aqueous solution is 0.01-0.5 mol / L;

[0025] Preferably, in step S1, during the precipitation process, an aqueous sodium hydroxide solution is slowly added dropwise to prevent local over-alkalinity, and the pH is controlled between 8 and 10 during the precipitation process, and the pH at the precipitation endpoint is controlled between 9 and 10.

[0026] The principle of preparing alumina-loaded cobalt hydroxide by liquid phase precipitation method is as follows: alumina and soluble cobalt salt are ultrasonically dispersed in water, and then sodium hydroxide solution is slowly added under controlled pH to precipitate cobalt hydroxide on alumina, wherein the cobalt hydroxide is fixed on the surface of alumina in the form of a precipitate.

[0027] Step S2: preparing alumina-supported cobalt by a reduction method.

[0028] In some embodiments, step S2 comprises the following steps:

[0029] The alumina-supported cobalt hydroxide obtained in step S1 is placed in a furnace (such as a tubular furnace) into which a reducing atmosphere is introduced for heating and reaction, and after the reaction is completed, alumina-supported cobalt (Al2O3 / Co) is obtained.

[0030] The principle of preparing alumina-loaded cobalt by reduction method is as follows: alumina-loaded cobalt hydroxide is placed in a tubular furnace, and a reduction reaction is carried out under certain temperature and hydrogen flow conditions to reduce the cobalt hydroxide to metallic cobalt, thereby preparing alumina-loaded cobalt.

[0031] Preferably, in step S2, the heating temperature is 500-700° C., and the reaction time is 3-5 h.

[0032] There are several benefits to setting the reduction reaction temperature in the range of 500-700°C. First, this temperature range is more suitable for the reduction of cobalt on the alumina support. Higher temperatures can promote the formation and lattice development of metal particles, which helps to improve its catalytic performance. In addition, higher temperatures also help to speed up the reaction rate, thereby shortening the reaction time. The appropriate reaction time can ensure that the metal particles are evenly distributed on the surface of the support and help control the size and distribution of the metal particles. The preferred reaction time is between 3-5h to ensure that sufficient reduction reaction occurs while avoiding excessive growth of metal particles due to over-reduction.

[0033] Preferably, in step S2, reducing gas hydrogen (H2) is introduced at a flow rate of 150-250 sccm.

[0034] As for the hydrogen flow rate, a higher hydrogen flow rate helps to ensure that a proper reducing atmosphere is maintained in the reaction system, thereby promoting the formation of metal particles, and a range of 150-250 sccm can provide sufficient hydrogen supply to promote the reduction reaction.

[0035] Therefore, these parameter ranges are selected to obtain uniform distribution of metal particles during the reduction reaction, promote their formation and lattice development, and ensure efficient reaction.

[0036] Step S3: depositing carbon nanotubes on cobalt using a vapor deposition method.

[0037] In some embodiments, step S3 comprises the following steps:

[0038] The alumina-loaded cobalt obtained in step S2 is placed in a heating furnace (such as a tubular furnace) into which a gaseous carbon source (methane) is introduced for reduction reaction. After the reaction is completed, an alumina-loaded cobalt / carbon nanotube composite material (Al2O3 / Co / CNT, where / represents and) is prepared.

[0039] The principle of depositing carbon nanotubes on alumina-supported cobalt by vapor deposition is as follows: methane is used as a carbon source in a tube furnace at a certain temperature to decompose and deposit on the surface of cobalt metal, thereby preparing an alumina-supported cobalt / carbon nanotube material.

[0040] Preferably, in step S3, the reduction reaction temperature is 600-850° C., and the reaction time is 1-2 h.

[0041] There are several benefits to setting the reaction temperature in the range of 600-850°C. This temperature range helps to accelerate the reaction rate, thereby shortening the reaction time, and is also conducive to the cracking of the carbon source and the growth of carbon nanotubes. The appropriate reaction time can ensure that the carbon material is evenly distributed on the surface of the carrier. The reaction time is selected between 1-2h to ensure sufficient reduction reaction while avoiding excessive reduction that causes excessive growth of carbon nanotubes.

[0042] Preferably, in step S3, the carbon source is methane (CH4) with a flow rate of 300-400 sccm.

[0043] As for the methane gas flow rate, a higher methane flow rate helps to ensure that an appropriate carbon source concentration is maintained in the reaction system, thereby promoting the formation of carbon nanotubes, and a range of 300-400 sccm can provide sufficient carbon source supply to promote the growth of carbon nanotubes.

[0044] Therefore, these parameter ranges are selected to ensure efficient reaction during the reduction reaction. At the same time, these conditions are also conducive to the cracking of the carbon source and the growth of carbon nanotubes, thereby preparing carbon nanotubes deposited on metal cobalt.

[0045] Step S4: preparing the lithium-replenishing diaphragm by spraying.

[0046] In some embodiments, step S4 comprises the following steps:

[0047] The alumina-loaded cobalt / carbon nanotube composite material obtained in step S3 is mixed with lithium sulfide, a dispersant, and a binder to prepare a uniform suspension solution, which is evenly coated on a base film (e.g., a polypropylene (PP) film) by spraying, and dried to remove the solvent to obtain a diaphragm. The diaphragm is then baked at a temperature of 30-50°C to allow the alumina-loaded cobalt, carbon nanotubes, and lithium sulfide to adhere to form a stable coating.

[0048] Preferably, the mass ratio of the alumina-supported cobalt / carbon nanotube composite material to the lithium sulfide, the dispersant, and the binder is 50-80:20-50:0.1-0.5:1-2.

[0049] Li2S and Co are lithium replenishment additives for the separator coating. They have a lithium storage capacity far higher than that of the positive electrode material, and the lithium desorption potential is lower than the maximum charging potential of the positive electrode, which provides a prerequisite for the possibility of lithium replenishment. The principle of lithium replenishment by the lithium replenishment coating is as follows: Li2S and Co remove Li during the first charging process. + , which migrates to the negative electrode as an additional lithium source to participate in the SEI film formation reaction and make up for the loss of active lithium ions in the positive electrode. 2- It combines with Co and releases electrons, which are then conducted out through the conductive effect of carbon nanotubes.

[0050] The specific electrochemical reaction process is as follows:

[0051] xCo+yLi2S→Co x S y +2yLi + +2ye -

[0052] After the lithium replenishment is successfully completed, the initial charge and discharge efficiency can be improved, thereby increasing the reversible capacity and energy density of the battery. x S y Maintaining electrochemical inertness within the battery operating voltage range will not affect subsequent battery performance.

[0053] The alumina-loaded cobalt, carbon nanotubes and lithium sulfide prepared by the present invention are attached to the diaphragm to form a stable coating, and the main advantages are: 1. By preparing alumina-loaded cobalt and carbon nanotubes, the thermal stability of the diaphragm can be improved and shrinkage at high temperatures can be inhibited. 2. Carbon nanotubes have the functions of selective permeability and conductive skeleton, which can promote the rapid migration of electrons / ions, thereby enhancing the fast charging performance of lithium-ion batteries. 3. Through the synergistic effect of lithium sulfide and cobalt, the product after lithium replenishment remains electrochemically inert, achieving stable lithium replenishment. A comprehensive solution is provided for the thermal stability of lithium-ion battery diaphragms at high temperatures, the rapid migration of lithium ions in the diaphragm and the energy density of lithium-ion batteries.

[0054] In a third aspect, the present invention provides a lithium-ion battery comprising the above-mentioned lithium-supplementing separator.

[0055] The preparation method of the lithium ion battery comprises the following steps:

[0056] Step 1: Prepare the positive and negative electrode slurries of lithium-ion batteries respectively. The positive electrode slurry components include positive electrode materials, binders and conductive agents; the negative electrode slurry components include negative electrode materials, binders, thickeners and conductive agents.

[0057] A positive electrode slurry for a lithium-ion battery includes a solid component and a solvent. The solid component includes a lithium iron phosphate positive electrode material, a binder polyvinylidene fluoride, and a conductive agent conductive carbon black. The mass percentages are respectively lithium iron phosphate (96-98%), a binder polyvinylidene fluoride (1-2%), and a conductive agent conductive carbon black (1-2%).

[0058] A negative electrode slurry for a lithium-ion battery includes a solid component and a solvent. The solid component includes graphite as a negative electrode material, styrene-butadiene rubber as a binder, sodium carboxymethyl cellulose as a thickener, and conductive carbon black as a conductive agent. The mass percentages are respectively graphite (94-97%) as a negative electrode material, styrene-butadiene rubber (1-2%) as a binder, sodium carboxymethyl cellulose (1-2%) as a thickener, and conductive carbon black (1-2%) as a conductive agent.

[0059] Step 2: Prepare the positive electrode and negative electrode of the lithium-ion battery by coating the positive and negative electrode slurries on the positive electrode collector and the negative electrode collector respectively.

[0060] Preferably, the positive electrode current collector is aluminum foil, and the negative electrode current collector is copper foil.

[0061] Preferably, the positive and negative electrode slurries are coated on the positive and negative electrode current collectors respectively, and then rolled, slit, die-cut and baked to obtain the product.

[0062] Step 3: Prepare lithium-ion batteries by stacking, packaging, injecting, wetting, forming, degassing, aging, capacity testing and sorting the positive and negative electrodes of lithium-ion batteries.

[0063] Preferably, the lithium-ion battery comprises an electrolyte, a separator, a shell, and a positive electrode and a negative electrode of the lithium-ion battery.

[0064] Preferably, the positive electrode and negative electrode of the lithium-ion battery are separated by a diaphragm, the electrolyte, the diaphragm and the positive electrode and negative electrode of the lithium-ion battery are located inside the shell, and the diaphragm is the above-mentioned lithium-supplementing diaphragm.

[0065] Preferably, the shell is a square soft bag or a square shell.

[0066] As a specific embodiment, the preparation method of the lithium ion battery is as follows:

[0067] Dissolve 100-200g PVDF in NMP solvent, then add lithium iron phosphate positive electrode material and conductive carbon black and mix them evenly. Among them, the positive electrode slurry of lithium-ion battery is lithium iron phosphate (96-98%), PVDF (1-2%) and conductive carbon black (1-2%) according to weight percentage. Dissolve 100-200g CMC in deionized water, then add graphite, conductive agent and SBR and mix them evenly. Among them, the negative electrode slurry of lithium-ion battery is graphite (94-97%), conductive agent (1-2%), CMC (1-2%) and SBR (1-2%) according to weight percentage.

[0068] The obtained positive electrode slurry of lithium-ion battery is coated on aluminum foil current collector, and the negative electrode slurry is coated on copper foil current collector. Finally, the positive and negative electrode sheets are manufactured through rolling, slitting, die-cutting and baking.

[0069] The positive and negative electrode sheets are assembled with the above-mentioned separator, electrolyte and shell to form a square shell lithium-ion battery.

[0070] Beneficial effects:

[0071] The present invention sequentially prepares a diaphragm comprising aluminum oxide loaded with cobalt, carbon nanotubes and a lithium sulfide coating by a precipitation method, a reduction method, a vapor deposition method and a spraying method. Aluminum oxide loaded with cobalt, carbon nanotubes and lithium sulfide have a synergistic effect, aluminum oxide can significantly improve the thermal stability of the diaphragm and inhibit the shrinkage of the diaphragm at high temperatures, lithium sulfide can achieve the effect of lithium replenishment as a lithium replenisher, and cobalt and sulfur combine to form a stable sulfide during the lithium replenishment process, thereby maintaining electrochemical inertness after the lithium replenishment is completed, and realizing stable lithium replenishment, carbon nanotubes have selective permeability to lithium ions, and as a conductive skeleton, can promote the rapid migration of electrons and ions, can enhance the fast charging performance of lithium ion batteries, so that lithium ion batteries take into account safety performance, energy density and fast charging performance.

[0072] The present invention has been described in detail above, but the above embodiments are only illustrative in nature and are not intended to limit the present invention. In addition, this article is not limited by any theory described in the above prior art or invention content or the following examples. BRIEF DESCRIPTION OF THE DRAWINGS

[0073] Figure 1 It is a schematic diagram of the process of preparing the lithium supplementing diaphragm of the present invention. DETAILED DESCRIPTION

[0074] The present invention is further described below in conjunction with examples. It should be noted that the following examples are provided for illustrative purposes only and do not constitute a limitation on the scope of protection claimed for the present invention.

[0075] Unless otherwise specified, the raw materials, reagents, methods, etc. used in the examples are conventional raw materials, reagents, methods in the art.

[0076] raw material:

[0077] Alumina powder was purchased from the market and had a particle size D50 of 0.5 μm.

[0078] Example 1

[0079] The preparation process of the diaphragm includes the following steps:

[0080] Take 2mmol of aluminum oxide (Al2O3) powder and 1mmol of cobalt chloride (CoCl2) in a beaker, add 100mL of deionized water, and ultrasonicate for 60min to make it evenly dispersed. 0.5mol / l sodium hydroxide (NaOH) aqueous solution, control the pH to be no more than 10 during the entire precipitation process, until Co is completely precipitated, and the pH at the precipitation end point is controlled at 10 (under the condition of not continuing to drop the NaOH aqueous solution, the pH of the solution is not reduced by continuing to stir), and aluminum oxide-loaded cobalt hydroxide (Al2O3 / Co(OH)2) is generated during the slow drop process. Secondly, the aluminum oxide-loaded cobalt hydroxide is placed in a tubular furnace, the reduction reaction temperature is set to 600℃, the reaction time is 4h, and the flow rate of the reducing gas hydrogen (H2) is 200sccm. After the reaction, aluminum oxide-loaded metal cobalt (Al2O3 / Co) is prepared. Furthermore, the aluminum oxide loaded with metal cobalt is placed in a tube furnace, the reduction reaction temperature is set to 750°C, the reaction time is 2h, and the flow rate of methane (CH4) is continued to be 400sccm. After the reaction is completed, carbon nanotubes (Al2O3 / Co / CNT) deposited on aluminum oxide loaded with metal cobalt are prepared; finally, the carbon nanotubes (70%) deposited on aluminum oxide loaded with metal cobalt are mixed evenly with PVP (0.2%), lithium sulfide (19.8%), PVDF (10%) and solvent NMP to prepare a suspension solution, which is evenly coated on the base film polypropylene (PP) by spraying. The coated diaphragm is dried to remove the solvent. The diaphragm is baked at a temperature of 30-50°C to form a stable coating.

[0081] Example 2

[0082] The preparation process of the diaphragm includes the following steps:

[0083] Take 1mmol of aluminum oxide (Al2O3) powder and 2mmol of cobalt chloride (CoCl2) in a beaker, add 100mL of deionized water, and ultrasonicate for 60min to make it evenly dispersed. 0.5mol / l sodium hydroxide (NaOH) aqueous solution, control the pH to be no more than 10 during the entire precipitation process, until Co is completely precipitated, and the pH at the precipitation end point is controlled at 10 (under the condition of not continuing to drop the NaOH aqueous solution, the pH of the solution is not reduced by continuing to stir), and aluminum oxide-loaded cobalt hydroxide (Al2O3 / Co(OH)2) is generated during the slow drop process. Secondly, the aluminum oxide-loaded cobalt hydroxide is placed in a tubular furnace, the reduction reaction temperature is set to 600℃, the reaction time is 4h, and the flow rate of the reducing gas hydrogen (H2) is 200sccm. After the reaction, aluminum oxide-loaded metal cobalt (Al2O3 / Co) is prepared. Furthermore, the aluminum oxide loaded with metal cobalt is placed in a tube furnace, the reduction reaction temperature is set to 750°C, the reaction time is 2h, and the flow rate of methane (CH4) is continued to be 400sccm. After the reaction is completed, carbon nanotubes (Al2O3 / Co / CNT) deposited on aluminum oxide loaded with metal cobalt are prepared; finally, the carbon nanotubes (64%) deposited on aluminum oxide loaded with metal cobalt are mixed evenly with PVP (0.2%), lithium sulfide (25.8%), PVDF (10%) and solvent NMP to prepare a suspension solution, which is evenly coated on the base film polypropylene (PP) by spraying. The coated diaphragm is dried to remove the solvent. The diaphragm is baked at a temperature of 30-50°C to form a stable coating.

[0084] Example 3

[0085] The preparation process of the diaphragm includes the following steps:

[0086] Take 1.5mmol of aluminum oxide (Al2O3) powder and 1.5mmol of cobalt chloride (CoCl2) in a beaker, add 100mL of deionized water, and ultrasonicate for 60min to make it evenly dispersed. 0.5mol / l sodium hydroxide (NaOH) aqueous solution, control the pH to be no more than 10 during the entire precipitation process, until Co is completely precipitated, and the pH at the precipitation end point is controlled at 10 (under the condition of not continuing to drop the NaOH aqueous solution, the pH of the solution is not reduced by continuing to stir), and aluminum oxide-loaded cobalt hydroxide (Al2O3 / Co(OH)2) is generated during the slow drop process. Secondly, the aluminum oxide-loaded cobalt hydroxide is placed in a tubular furnace, the reduction reaction temperature is set to 600℃, the reaction time is 4h, and the flow rate of the reducing gas hydrogen (H2) is 200sccm. After the reaction, aluminum oxide-loaded metal cobalt (Al2O3 / Co) is prepared. Furthermore, the aluminum oxide loaded with metal cobalt is placed in a tube furnace, the reduction reaction temperature is set to 750°C, the reaction time is 2h, and the flow rate of methane (CH4) is continued to be 400sccm. After the reaction is completed, carbon nanotubes (Al2O3 / Co / CNT) deposited on aluminum oxide loaded with metal cobalt are prepared; finally, the carbon nanotubes (68.7%) deposited on aluminum oxide loaded with metal cobalt are mixed evenly with PVP (0.2%), lithium sulfide (21.1%), PVDF (10%) and solvent NMP to prepare a suspension solution, which is evenly coated on the base film polypropylene (PP) by spraying. The coated diaphragm is dried to remove the solvent. The diaphragm is baked at a temperature of 30-50°C to form a stable coating.

[0087] Comparative Example 1

[0088] The difference from Example 2 is that cobalt chloride (CoCl2) is replaced by nickel chloride (NiCl2) to prepare carbon nanotubes deposited on alumina-supported nickel (Al2O3 / Ni / CNT). Carbon nanotubes deposited on alumina-supported nickel (64%), PVP (0.2%), lithium sulfide (25.8%), PVDF (10%) and solvent NMP are uniformly mixed to prepare a suspension solution, which is uniformly coated on the base film polypropylene (PP) by spraying.

[0089] Comparative Example 2

[0090] The difference from Example 2 is that lithium sulfide (25.8%) is evenly mixed with PVP (0.2%), PVDF (74%) and solvent NMP to prepare a suspension solution, which is evenly coated on the base film polypropylene (PP) by spraying.

[0091] Comparative Example 3

[0092] The difference from Example 2 is that carbon nanotubes (64%) are deposited on alumina-loaded metal cobalt, mixed evenly with PVP (0.2%), PVDF (35.8%) and solvent NMP to prepare a suspension solution, which is evenly coated on the base film polypropylene (PP) by spraying.

[0093] Comparative Example 4

[0094] The difference from Example 2 is that the alumina-loaded metal cobalt (Al2O3 / Co) does not undergo carbon nanotube deposition, but the alumina-loaded metal cobalt (64%) is directly mixed with PVP (0.2%), PVDF (35.8%) and solvent NMP to prepare a suspension solution, which is then evenly coated on the base film polypropylene (PP) by spraying.

[0095] Comparative Example 5

[0096] The difference from Example 2 is that the diaphragm is polypropylene (PP) without coating material.

[0097] Comparative Example 6

[0098] The difference from Example 2 is that the diaphragm is polyethylene (PE) without coating material.

[0099] The diaphragms obtained in the examples and comparative examples were used to prepare lithium-ion batteries in the following manner:

[0100] Dissolve 100g PVDF in NMP solvent, then add lithium iron phosphate positive electrode material and conductive carbon black and mix them evenly. Among them, the lithium ion battery positive electrode slurry is lithium iron phosphate (97%), PVDF (1.6%) and conductive carbon black (1.4%) according to weight percentage. Dissolve 100g CMC in deionized water, then add graphite, conductive agent and SBR and mix them evenly. Among them, the lithium ion battery negative electrode slurry is graphite (95.2%), conductive agent (1%), CMC (1.8%) and SBR (2%) according to weight percentage.

[0101] The obtained positive electrode slurry of lithium-ion battery is coated on aluminum foil current collector, and the negative electrode slurry is coated on copper foil current collector. Finally, the positive and negative electrode sheets are manufactured through rolling, slitting, die-cutting and baking.

[0102] The positive and negative electrode sheets are assembled with the above-mentioned separator, electrolyte and shell to form a square shell lithium-ion battery.

[0103] The energy density, first efficiency, 2C rate charge, 3C rate discharge, change in diaphragm thickness after testing, and 400-week 4C charge cycle performance of the lithium-ion battery were measured respectively. The results are shown in Table 1 below.

[0104] Table 1

[0105]

[0106] Through the comparison results of the energy density, first effect, 2C rate charging, 3C rate discharging, the change of diaphragm thickness before and after the test, and 400 cycles of 4C stage charging and cycling of the lithium ion batteries of the above Example 1, Example 2, Example 3, Comparative Example 1 and Comparative Example 2, it can be seen that the lithium ion battery diaphragm coating material of Example 2 has good characteristics, which are mainly manifested in that the energy density, first effect, 2C rate charging, 3C rate discharging, the change of diaphragm thickness before and after the test, and 400 cycles of 4C stage charging and cycling of the lithium ion battery have good performance, taking into account energy density, safety performance and fast charging performance. It is shown that alumina loaded with cobalt, carbon nanotubes and lithium sulfide can significantly improve the thermal stability of the diaphragm and inhibit the shrinkage of the diaphragm at high temperatures. Lithium sulfide can be used as a lithium replenisher to achieve the effect of lithium replenishment. During the lithium replenishment process, cobalt and sulfur combine to form stable sulfides, thereby maintaining electrochemical inertness after the lithium replenishment is completed, thereby achieving stable lithium replenishment. Carbon nanotubes have selective permeability to lithium ions, and as a conductive skeleton, they can promote the rapid migration of electrons and ions, which can enhance the fast charging performance of lithium-ion batteries, so that the prepared lithium-ion batteries have both safety performance, energy density and fast charging performance.

[0107] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit them. Although the present invention has been described in detail with reference to the above embodiments, those skilled in the art should understand that the technical solutions described in the above embodiments may be modified, or some or all of the technical features thereof may be replaced by equivalents, without departing from the spirit and essence of the claims of the present invention; and these modifications or replacements are still within the scope defined by the claims of the present invention.

Claims

1. A lithium supplementing diaphragm, characterized in that: The invention comprises a base film and a lithium supplement coating attached to at least one side of the base film. The components of the lithium supplement coating include aluminum oxide loaded cobalt, carbon nanotubes and lithium sulfide, wherein the carbon nanotubes are attached to the metal cobalt.

2. A method for preparing a lithium supplementing diaphragm according to claim 1, characterized in that: The following steps are involved: Step S1: using aluminum oxide and cobalt salt as raw materials, preparing aluminum oxide-supported cobalt hydroxide by liquid phase precipitation method; Step S2: heating the alumina-supported cobalt hydroxide obtained in step S1, and preparing alumina-supported cobalt metal by a reduction method; Step S3: using the aluminum oxide-supported cobalt metal obtained in step S2 as a raw material, adding a carbon source, and reducing and depositing carbon nanotubes on the aluminum oxide-supported cobalt metal by chemical vapor deposition to obtain an aluminum oxide-supported cobalt / carbon nanotube composite material; Step S4: uniformly mix the alumina-loaded cobalt / carbon nanotube composite material obtained in step S3 with a dispersant, lithium sulfide, and a binder, and spray the mixture onto at least one side of the base film to obtain a lithium-supplementing separator.

3. The preparation method according to claim 2, characterized in that: Step S1 includes the following steps: Alumina powder and cobalt salt are placed in a beaker, deionized water is added thereto, and the powder is dispersed evenly by ultrasound. Then, a sodium hydroxide aqueous solution is slowly added to the dispersed liquid, and alumina-loaded cobalt hydroxide is generated during the slow dropwise precipitation process.

4. The preparation method according to claim 3, characterized in that: The cobalt salt in step S1 is one or more of cobalt chloride, cobalt sulfate, and cobalt nitrate; The molar ratio of aluminum oxide to cobalt salt is 1-2:1-2; The concentration of the sodium hydroxide aqueous solution is 0.01-0.5 mol / L, the pH is controlled between 8-10 during the precipitation process, and the pH at the precipitation endpoint is controlled between 9-10.

5. The preparation method according to claim 2, characterized in that: Step S2 includes the following steps: The alumina-supported cobalt hydroxide obtained in step S1 is placed in a furnace into which a reducing atmosphere is introduced for heating and reaction, and after the reaction is completed, alumina-supported cobalt is obtained.

6. The preparation method according to claim 5, characterized in that: In step S2, the heating temperature is 500-700°C and the reaction time is 3-5h; In step S2, hydrogen is introduced as a reducing gas with a flow rate of 150-250 sccm.

7. The preparation method according to claim 2, characterized in that: Step S3 includes the following steps: The alumina-supported cobalt obtained in step S2 is placed in a heating furnace into which a gaseous carbon source is introduced for reduction reaction, and after the reaction is completed, an alumina-supported cobalt / carbon nanotube composite material is prepared.

8. The preparation method according to claim 7, characterized in that: In step S3, the reduction reaction temperature is 600-850°C and the reaction time is 1-2h; In step S3, the carbon source is methane, and the flow rate is 300-400 sccm.

9. The preparation method according to claim 2, characterized in that: Step S4 includes the following steps: The alumina-loaded cobalt / carbon nanotube composite material obtained in step S3 is mixed with lithium sulfide, a dispersant, and a binder to prepare a uniform suspension solution, which is evenly coated on the base film by spraying, dried to remove the solvent, and then the diaphragm is baked at a temperature of 30-50°C to form a stable coating.

10. A lithium ion battery, characterized in that: The invention comprises the lithium-supplementing diaphragm according to claim 1, or the lithium-supplementing diaphragm prepared by the preparation method according to any one of claims 2 to 9.

Citation Information

Cited By

  • Ceramic composite lithium supplementing diaphragm as well as preparation method and application thereof

    CN120657372A

  • Ceramic composite lithium supplementing diaphragm, preparation method and application thereof

    CN120657372B